The effect of the presence tutorials in the academic performance of the administration students of a university of the north of Mexico - Armenta Zazueta, Lizeth; Quiroz Campas, Celia Yaneth; Cota Valenzuela, Laura Violeta (Unidad Editorial UPTC, 2020)
The purpose of the study was to identify the effect of the face-to-face tutoring program of undergraduate students in Administration on academic performance, as well as its level of student satisfaction with the program. The research questions were: (a) what are the aspects of the institutional tutoring program that impact on the academic performance of the students? (B) What is the satisfaction stage from the tutored about the tutoring institutional program attended? and (c) what effect does the institutional mentoring program have on the academic performance of administration students during their scholar journey? The methodology used in this study was based on the quantitative approach, non-experimental with a transactional design. 63 eight semester students participated, and they attended the tutoring program. The Pearson correlation test was used for the aspects included in the tutoring program and the academic performance of the students. The results indicate that there is no significant relation between the aspects that the tutorial program covers and the academic performance, however, is a high rate student satisfaction with the tutoring program. In the results of Pearson´s correlation test between the aspects of the program and the general average, no significant relation was found in the aspects covered by the program. As a conclusion, the institutional tutoring program does not have a statistically significant relation in the students' academic performance, in contrast to student satisfaction, which was favorable to the tutoring program. Key words: Effect, student, academic performance, satisfaction, tutor Code JEL: I20, I21, I23 Received: 24/06/2019. Accepted: 10/02/2020.  Published: 27/04/2020